The Impact of Lean Leadership on the Creative Work Behavior: Perceived Organizational Support as the Moderator variable. An analytical study in the Iraqi health sector. - Al-hadrawi, Rafid Hameed; Al-Abedi , Mohammed Hamza (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to test the effect of lean leadership (LL) on the creative work behavior (CWB) of employees through the moderating role of perceived organizational support (POS). The two researchers adopted the descriptive analytical approach to obtain and analyze data. The Iraqi health sector represented a field for the applied side of the study as the medical city of Imam Hussein in the Holy province of Karbala represented the research community, from which a random sample of medical and nursing staffs was selected; (302) employees. The two researchers used the modeling of the structural equation SEM in building the research model and testing its hypotheses. The results showed that lean leadership has a positive moral effect on creative work behavior. There is also a positive effect of perceived organizational support on creative work behavior. In addition to that, the results proved a positive contribution of the interactive variable, the perceived organizational support in the relationship between lean leadership and creative work behavior and increased the power of influence between them at the current level of research. Therefore, lean leadership has an important and effective role in finding and creating enhanced opportunities for creative behavior for medical and nursing staff on the one hand and Reducing the costs of providing service and health care on the other. through the interactive impact of perceived organizational support by assigning and assisting individuals in order to achieve and enhance thinking outside the box and unconventional behavior in their performance and encouraging them to distinguish as individuals or groups to improve the service and health care provided The lowest possible costs.